Safe approaches to modulating the immune response in recurrent acute respiratory infections in young children - D. A. Khavkina; T. A. Ruzhentsova; P. V. Chukhliaev; A. A. Garbuzov (Лечащий Врач)
The article presents materials on the effectiveness and safety of food products enriched with pre – and probiotic components, vitamins and trace elements for the prevention of acute respiratory infections (ARI) and as a therapeutic food in young children. Data on the role of bifidobacteria BB-12, inulin, vitamins and trace elements in the formation of the immune response are presented. The results of modern studies confirming the importance of these components in childhood are shown. Data on products enriched with components necessary for the prevention of acute respiratory infections are presented. It was shown that preventive intake of food products enriched with bifidobacteria BB-12, inulin, vitamins, macro-and microelements calcium, D3, safely modulates the activity of the immune system, which provides prevention of repeated episodes of ari in young children. The inclusion in the diet of foods enriched with probiotics, vitamins and trace elements in ARI significantly accelerates recovery and the period of convalescence. Fermented milk drink immunobaby for children older than 8 months, enriched with prebiotic (inulin), sourdough of lactic acidophilus bacilli, probiotic (bifidobacteria BB-12), vitamin and mineral complex containing Zn and vitamin D3, can be recommended for permanent, preventive and therapeutic nutrition of young children. Juice-containing drink for children older than 12 months enriched with prebiotic – inulin, minerals (calcium, iron) and vitamins (C, E, A, D3) is an additional source of necessary trace elements both during the period of ARI disease and during convalescence. The effectiveness of the drink is clinically proven. The composition of drinking yoghurts for children older than 8 months, enriched with prebiotic – inulin, and probiotic (bifidobacteria BB-12) can provide natural aid to digestion both in the acute period of infection, with pronounced antibiotic therapy, and for preventive purposes. The effectiveness is clinically proven.